Identification and Expression Profile of Olfactory Receptor Genes Based on Apriona germari (Hope) Antennal Transcriptome - Qian, Jia-Li; Mang, Ding-Ze; Lv, Guo-Chang; Ye, Jia; Li, Zhao-Qun; Chu, Bo; Sun, Long; Liu, Yu-Jun; Zhang, Long-Wa (Frontiers in Physiology, 2020)
Insects’ olfactory receptor plays a central role in detecting chemosensory information from the environment. Odorant receptors (ORs) and ionotropic receptors (IRs) are two types of olfactory receptors, and they are essential for the recognition of ligands at peripheral neurons. Apriona germari (Hope) (Coleoptera: Cerambycidae) is one of the most serious insect pests that cause damage to economic trees and landscaping trees, resulting in massive environmental damages and economic losses. Olfactory-based management strategy has been suggested as a promising strategy to control this wood-boring beetle. However, the olfactory perception mechanism in A. germari is now almost unknown. In the present study, RNA sequencing analysis was used to determine the transcriptomes of adult A. germari antennae. Among 36,834 unigenes derived from the antennal assembly, we identified 42 AgerORs and three AgerIRs. Based on the tissue expression pattern analysis, 27 AgerORs displayed a female-biased expression. Notably, AgerOR3, 5, 13, 33, and 40 showed a significant female-biased expression and were clustered with the pheromone receptors of Megacyllene caryae in the phylogenetic tree, suggesting that these AgerORs could be potential pheromone receptors for sensing male-produced sex pheromones in A. germari. The AgerIRs expression profile demonstrated that AgerIR2 had high expression levels in male labial palps, suggesting that this receptor may function to detect female-deposited trail-sex pheromone blend of A. germari. In addition, the phylogenetic tree showed that the Orco gene of five cerambycidae species was highly conservative. These results provide a foundation for further studies on the molecular mechanisms of olfactory chemoreception in A. germari apart from suggesting novel targets for the control of this pest in the future.